Fe(III) bioreduction kinetics in anaerobic batch and continuous stirred tank reactors with acidophilic bacteria relevant for bioleaching of limonitic laterites - Hubau, Agathe; Joulian, Catherine; Tris, Hafida; Pino-Herrera, Douglas; Becquet, Camille; Guezennec, Anne-Gwénaëlle (Frontiers in Microbiology, 2024)
In the framework of the H2020 project CROCODILE, the recovery of Co from oxidized ores by reductive bioleaching has been studied. The objective was to reduce Fe(III) to Fe(II) to enhance the dissolution of Co from New-Caledonian limonitic laterites, mainly composed of goethite and Mn oxides. This study focused on the Fe(III) bioreduction which is a relevant reaction of this process. In a first step, biomass growth was sustained by aerobic bio-oxidation of elemental sulfur. In a second step, the biomass anaerobically reduced Fe(III) to Fe(II). The last step, which is not in the scope of this study, was the reduction of limonites and the dissolution of metals. This study aimed at assessing the Fe(III) bioreduction rate at 35 °C with a microbial consortium composed predominantly of Sulfobacillus (Sb.) species as the iron-reducers and Acidithiobacillus (At.) caldus. It evaluated the influence of the biomass concentration on the Fe(III) bioreduction rate and yield, both in batch and continuous mode. The influence of the composition of the growth medium on the bioreduction rate was assessed in continuous mode. A mean Fe(III) bioreduction rate of 1.7 mg.L-1.h-1 was measured in batch mode, i.e. 13 times faster than the abiotic control (0.13 mg.L-1.h-1). An increase in biomass concentrations in the liquid phase from 4.108 cells.mL-1 to 3.109 cells.mL-1 resulted in an increase of the mean Fe(III) bioreduction rate from 1.7 to 10 mg.L-1.h-1. A test in continuous stirred tank reactors at 35 °C resulted in further optimization of the Fe(III) bioreduction rate which reached 20 mg.L-1.h-1. A large excess of nutrients enabled to obtain higher kinetics. The determination of this kinetics is essential for the design of a reductive bioleaching process.